Role of type-1 11beta-hydroxysteroid dehydrogenase in detoxification processes. - Maser, E; Oppermann, U (1997)
Carbonyl reduction is a significant step in the biotransformation leading to the elimination, of endogenous and exogenous aldehydes, ketones and quinones. This reaction is mediated by members of the aldo-keto reductase and short-chain dehydrogenase/reductase (SDR) superfamilies. The essential role of these enzymes in protecting organisms from damage by the accumulation of toxic carbonyl compounds is generally accepted, although their physiological roles are not always clear. Recently, the SDR enzyme 11beta-hydroxysteroid dehydrogenase-1 has been identified to perform an important role in the detoxification of non-steroidal carbonyl compounds, in addition to metabolising its physiological glucocorticoid substrates. This review summarises the current knowledge of type-1 11beta-hydroxysteroid dehydrogenase and discusses possible substrate/inhibitor interactions. They might impair either the physiological function of glucocorticoids or the detoxification of non-steroid carbonyl compounds.